Substrates on germinative seed processes in Tabebuia roseo-alba (Ridl.) Sandwith) And Tabebuia serratifolia (Vahl) G. Nicholson - Silva, Regimonica Craveiro da; Aguiar, Bruno Aurélio Campos; Gomes, Taiuan Bruno Almeida; Santos, Bárbara Maria Martins; Fonseca, Euclides Figuerêdo; Souza, Priscila Bezerra de (Scientia Agraria Paranaensis, 2020)
Among the constituents of Brazilian flora, the ipes, belonging to the Bignoneaceae family, occur widely, and therefore do not occupy a single habitat. This group species has various values, including economic, ornamental and medicinal. The objective of this work was to evaluate the effect of various substrates on the seed germination process of Tabebuia roseo-alba (Ridl.) Sandwith) (ipê rosa) and T. serratifolia (Vahl) G. Nicholson (ipê amarelo). The experiment was carried out with BOD type germinators, adjusted to a constant temperature of 30ºC, with a photoperiod of twelve hours daily. The seeds were distributed in transparent acrylic boxes (Gerbox) and conditioned under the substrates: carbonized rice husk (CRH), commercial substrate (CS) Bioflora, washed sand (WS) and vermiculite (V). The treatments were distributed in a 2 x 5 factorial scheme (two species and five substrates), with four replications. At 30 days, the final percentage of emergence (% E) or the total percentage of seeds emerged up to 30 days after sowing was calculated. In general, T. serratifolia seeds showed relatively higher values of emergence percentage and emergence speed. The treatment containing 100% commercial substrate showed the best results for both species in terms of percentage and emergence speed, however it can be inferred that the washed sand substrate showed similar values for the yellow ipê under the tested conditions.